Offshore outsourcing in large companies: motivations and risks perceived - Varajão, J. E. (2014)
When companies opt for information systems (IS) outsourcing, within the set of contracted services, they can contract their entire service needs to onshore suppliers or to offshore companies, or part of these services can be contracted to onshore suppliers and the other part to offshore suppliers. The offshore outsourcing reveals itself nowadays as an important strategic option to IS management optimization. This paper presents and discusses the main results of a survey that was carried out in Portugal to determine several aspects of offshore practice in large companies. It allowed the identification of the services more frequently contracted, the most common motivations for choosing offshore suppliers and the main risks perceived by companies. This research contributes to a better understanding of the IS offshore market, enabling client companies and vendors to improve their strategic business action.